Diversity and Ecological Role Bryophyte in Sesaot Forest, Lombok, West Nusa Tenggara - Nuroh Bawaihaty; Istomo .; Iwan Hilwan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Diversity of mosses in Sesaot forest, Lombok, West Nusa Tenggara has 22 spesies, 12 family, and 3 classes. Diversity of mosses is the most common in the primary forest are 18 spesies, in fruit forest there are 12 spesies. And in the secondary forest are 7 species, there are 4 species contained in 3 areas, namely thuidium sp., barbella sp., calymperes sp., and lejeunea sp. Kind of mosses that mostly found is lejeunea sp., family is lejeuneaceae and classes is hepatice. And kind of mosses that lessly found is taxithelium sp., family is sematophyllaceae, and classes is music. Calyptotherium sp., family is entodontaceae, and classes is music. Plagiochila sp., family is lophoziaceae, and classes is music, and bazzania sp., family is lepidoziaceae, and classes hepatice. The condition of forest affect to the growth of mosses and its ecological roles in forest ecosystem. The mosses includes in pioneer plants, it is evidenced by many mosses that grow on fallen trees.